2005
DOI: 10.1366/0003702053585363
|View full text |Cite
|
Sign up to set email alerts
|

Method for Quantitative Determination of Spatial Polymer Distribution in Alginate Beads Using Raman Spectroscopy

Abstract: A new method based on Raman spectroscopy is presented for non-invasive, quantitative determination of the spatial polymer distribution in alginate beads of approximately 4 mm diameter. With the experimental setup, a two-dimensional image is created along a thin measuring line through the bead comprising one spatial and one spectral dimension. For quantitative analysis of the Raman spectra, the method of indirect hard modeling was applied to make use of the information contained in the entire recorded spectra. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…For the bead production process used in this work, the alginate density distribution has been measured using Raman spectroscopy (Heinemann et al, 2005). The quadratic equation 4-14 was used to fit the alginate density profile, where w alg is the alginate mass fraction, lg a w the average alginate mass fraction, d a model parameter to be fitted, and R the bead radius.…”
Section: Model Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…For the bead production process used in this work, the alginate density distribution has been measured using Raman spectroscopy (Heinemann et al, 2005). The quadratic equation 4-14 was used to fit the alginate density profile, where w alg is the alginate mass fraction, lg a w the average alginate mass fraction, d a model parameter to be fitted, and R the bead radius.…”
Section: Model Developmentmentioning
confidence: 99%
“…Since Ca-alginate beads exhibit an inhomogeneous density distribution (Heinemann et al, 2005), κ-carrageenan is chosen as hydrogel material. In contrast to Ca-alginate, the κ-carrageenan hydrogel beads are produced by cryogelation, which results in a homogeneous density distribution.…”
Section: Diffusion In κ-Carrageenan Hydrogel Beads 421 Introductionmentioning
confidence: 99%
“…For example, IR studies have revealed that Ca 2+ ions preferentially bind to G blocks in agreement with other techniques. Confocal Raman spectroscopy (CRM) is a more powerful technique than IR because it is characterised by a high specificity, revealing usually sharper and clearer bands than IR spectra and low water background 20, 21. Raman spectroscopy can be employed for the determination of M/G ratio in alginic acid 22.…”
Section: Introductionmentioning
confidence: 99%
“…This suspension is then compartmentalized into single small droplets by one of several available techniques (13)(14)(15). Next, the droplets are reinforced by gelation, which in the case of agaroses is induced by cooling (16) and in the case of alginates by chemically induced cross linking (17,18). As a result, cells become immobilized within the microcarrier.…”
mentioning
confidence: 99%